Exciton‐Stimulated Molecular Transformation in Organic Light‐Emitting Diodes. (21st August 2014) - Chang, Yi‐Lu; Rao, Ying‐Li; Gong, Shaolong; Ingram, Grayson L.; Wang, Suning; Lu, Zheng‐Hong
<x xml:space="preserve">Abstract</x> An exciton‐stimulated molecular transformation in an organic light‐emitting diode (OLED) on a time scale of a few seconds under electrical bias is shown to reach nearly 100% under standard operating conditions, leading to color switching. It is reversible in both a thin film and an OLED when sufficient thermal energy is supplied. Such an exciton‐stimulated molecular transformation suggests a new process which may be exploited for applications such as electrochromic and memory devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>